2014
DOI: 10.1159/000360624
|View full text |Cite
|
Sign up to set email alerts
|

Oxalate Quantification in Hemodialysate to Assess Dialysis Adequacy for Primary Hyperoxaluria

Abstract: Background: Patients with primary hyperoxaluria (PH) overproduce oxalate which is eliminated via the kidneys. If end-stage kidney disease develops they are at high risk for systemic oxalosis, unless adequate oxalate is removed during hemodialysis (HD) to equal or exceed ongoing oxalate production. The purpose of this study was to validate a method to measure oxalate removal in this unique group of dialysis patients. Methods: Fourteen stable patients with a confirmed diagnosis of PH on HD were included in the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
1
21
0
Order By: Relevance
“…Prior to transplantation, patients with ESRD require intensive dialysis to avoid systemic oxalosis. Conventional dialysis (4 h, three times a week) provides adequate oxalate clearance and can lead to systemic oxalate deposition in joints, retina, heart, skin, bone, and bone marrow [ 5 , 10 , 11 ]. There are few data to indicate the dialysis dose needed to prevent these complications.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prior to transplantation, patients with ESRD require intensive dialysis to avoid systemic oxalosis. Conventional dialysis (4 h, three times a week) provides adequate oxalate clearance and can lead to systemic oxalate deposition in joints, retina, heart, skin, bone, and bone marrow [ 5 , 10 , 11 ]. There are few data to indicate the dialysis dose needed to prevent these complications.…”
Section: Discussionmentioning
confidence: 99%
“…There are few data to indicate the dialysis dose needed to prevent these complications. In one study of 14 hemodialysis patients with PH1, intensive dialysis (5–6 sessions/week) provided mean weekly oxalate removal of 11.13 ± 6.88 mmol/week, which the authors estimated was adequate, when combined with residual renal excretion, to remove daily oxalate production [ 11 ]. However, plasma oxalate levels remained markedly above normal (75.1 ± 33.4 μmol/L, normal < 1.6 μmol/L).…”
Section: Discussionmentioning
confidence: 99%
“…Oxalate is reasonably well-removed by dialysis, even so, the amount removed in a standard 3 day per week HD treatment can not keep up with production rates, in part because oxalate is only removed from the blood compartment, and equilibration of plasma oxalate with extravascular compartments like bone is slower [13]. Thus, more frequent HD treatment are more efficient than longer but less frequent HD regimens [14]. Although dialysis modalities are generally inadequate for the clearence of oxalate load, in a study showed that combining HD and PD prior to transplantation facilitates the mobilization of oxalic depositions with decreased oxalate and favors better short-and long term kidney graft survival (15).…”
Section: Discussionmentioning
confidence: 99%
“…Plasma oxalate levels rise, and insoluble calcium oxalate crystals are deposited in tissues throughout the body, including the kidney, heart, bone, blood vessels, retina, muscle, skin, and nerve. Hemodialysis is needed to remove oxalate from the body, but removal is incomplete, and even when it is intensive, dialysis is often insufficient to prevent progressive systemic oxalate deposition . Because oxalate removal with dialysis is incomplete, the treatment of choice for patients with PH1 and poor kidney function is combined liver/kidney transplantation.…”
mentioning
confidence: 99%
“…Hemodialysis is needed to remove oxalate from the body, but removal is incomplete, and even when it is intensive, dialysis is often insufficient to prevent progressive systemic oxalate deposition. [2][3][4] Because oxalate removal with dialysis is incomplete, the treatment of choice for patients with PH1 and poor kidney function is combined liver/kidney transplantation. Liver transplantation is required in the majority of PH1 patients to restore the hepatic enzyme defect and protect the renal allograft from recurrent oxalate nephropathy.…”
mentioning
confidence: 99%